2013
DOI: 10.5194/bg-10-851-2013
|View full text |Cite
|
Sign up to set email alerts
|

The Australian terrestrial carbon budget

Abstract: Abstract. This paper reports a study of the full carbon (C-CO2) budget of the Australian continent, focussing on 1990–2011 in the context of estimates over two centuries. The work is a contribution to the RECCAP (REgional Carbon Cycle Assessment and Processes) project, as one of numerous regional studies. In constructing the budget, we estimate the following component carbon fluxes: net primary production (NPP); net ecosystem production (NEP); fire; land use change (LUC); riverine export; dust export; harvest … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 51 publications
(59 reference statements)
5
91
1
Order By: Relevance
“…The run based on the CASA-GFED model only shows very limited variability in the 3 monthly biosphere fluxes, while the GOSAT-based one shows a strong drop starting in 2010 and lasting until early 2012. Based on the calculated 3 monthly fluxes in Figure 4, we estimate the strength of the enhancement of the carbon sink to be roughly 0.77 ± 0.10 Pg C yr −1 or 1.5 ± 0.2 Pg C for the whole period of April 2010 to December 2011, which corresponds to 25% of the total multiyear (1990-2011) average GPP of the Australian biosphere and 1000% of the average annual net ecosystem production [Haverd et al, 2013]. Compared to the enhanced LPJ sink reported in Poulter et al [2014], we derived a 2011 enhancement in the sink of 0.86 ± 0.15 Pg C, which is very similar to the 0.79 Pg C quoted in that publication.…”
Section: Biosphere Model Comparisonmentioning
confidence: 98%
“…The run based on the CASA-GFED model only shows very limited variability in the 3 monthly biosphere fluxes, while the GOSAT-based one shows a strong drop starting in 2010 and lasting until early 2012. Based on the calculated 3 monthly fluxes in Figure 4, we estimate the strength of the enhancement of the carbon sink to be roughly 0.77 ± 0.10 Pg C yr −1 or 1.5 ± 0.2 Pg C for the whole period of April 2010 to December 2011, which corresponds to 25% of the total multiyear (1990-2011) average GPP of the Australian biosphere and 1000% of the average annual net ecosystem production [Haverd et al, 2013]. Compared to the enhanced LPJ sink reported in Poulter et al [2014], we derived a 2011 enhancement in the sink of 0.86 ± 0.15 Pg C, which is very similar to the 0.79 Pg C quoted in that publication.…”
Section: Biosphere Model Comparisonmentioning
confidence: 98%
“…2.3.4. The RECCAP regions include North America (NA; King et al, 2015), South America (SA; Gloor et al, 2012), Europe (EU; Luyssaert et al, 2012), Africa (AF; Valentini et al, 2014), Russia (RU; Dolman et al, 2012), East Asia (EA; Piao et al, 2012), South Asia (SAs; Patra et al, 2013), and Australia (AU; Haverd et al, 2013). No regional study is yet available for Southeast Asia (SEA).…”
Section: Reccap Over Landmentioning
confidence: 99%
“…Quantifying North America's net land-atmosphere CO 2 exchange, potentially offsetting at least a portion of North America's CO 2 emissions, is an important element of understanding and quantifying North America's contribution to the accelerating increase in atmospheric CO 2 concentrations (Le Quéré et al, 2014). Our approach was guided by (a) ; (b) RECCAP syntheses for other regions (Dolman et al, 2012;Gloor et al, 2012;Haverd et al, 2013;Luyssaert et al, 2012;Patra et al, 2013;Piao et al, 2012;Valentini et al, 2014); (c) guidelines found at the REC-CAP website (http://www.globalcarbonproject.org/reccap/); and (d) personal communications with J. G. as Coordinator of the RECCAP Science Steering Committee. This study focuses on estimates of land-atmosphere CO 2 exchange over Canada, the United States and Mexico.…”
mentioning
confidence: 99%